PERTANGGUNGJAWABAN PIDANA PELAKU PERETASAN WEBSITE BERDASARKAN HUKUM POSITIF INDONESIA - Tegar Gempa Nusantara (2023)
In era with easy access to the internet and all other electronic devices, hackers are vulnerable to websites. Website hacking is an attempt to be connected to a website so that it can be accessed without the permission or approval of the website owner. The perpetrators of hacking websites in their actions so that they can be subject to criminal sanctions must pay attention to aspects of criminal responsibility so that they are in line with the rules of criminal punishment. In understanding how the criminal responsibility of website hacking perpetrators in Indonesia is implemented, we will compare the aspects of criminal responsibility of two district court decisions, namely Decision Number: 9/Pid.Sus/2021/PN Pli and Number: 527/Pid.Sus/2020/PN Smn. The method used in this study is normative juridical through a statute approach, a case approach, and a conceptual approach. The data collection technique in this study was a literature study. Based on the results of the research, it was found that the implementation of website hacking accountability in Indonesia is contained in the Electronic Information and Transaction Law and the Personal Data Protection Act, both matches Decision Number: 9/Pid.Sus/2021/PN Pli and Number: 527/Pid. Sus/2020/PN Smn in the aspect of criminal liability there are similarities in the form of the perpetrators of hacking who are individuals who are equally competent at law, the criminal elements of website hacking are fulfilled, there are no justifications and/or excuses, laws and regulations used and differences in the type websites that were hacked, the articles used to ensnare the perpetrators of the hacking crime committed, and the judge's considerations in imposing criminal sanctions.